The Implementation of Local Cultural Identity in Form of 23 Character Values Taught in Islamic Boarding School - Sokip, Sokip (Digital Press Social Sciences and Humanities, 2019)
Education has very important role in term to build student personality and to help them having character values. This role to handle young generation cases nowadays, such losing local identity and preferring to western culture. Educational institution must insert character values in learning process. One of the institutions meant is Islamic Boarding School. In this case the writer wants to prove that Islamic Boarding School is suitable choice of school in term of character development for students because in teaching inserts several character values inside. To find the values, the writer uses library research method on chosen yellow books of Islamic Boarding School. As the result, to develop local identity in young generation, then it is found twenty-three character values that are being taught in Islamic Boarding School based on four yellow books studied.